Fine‐Tuning Covalent Inhibition of Bacterial Quorum Sensing. (15th March 2016) - Amara, Neri; Gregor, Rachel; Rayo, Josep; Dandela, Rambabu; Daniel, Erik; Liubin, Nina; Willems, H. Marjo E.; Ben‐Zvi, Anat; Krom, Bastiaan P.; Meijler, Michael M.
Abstract: Emerging antibiotic resistance among human pathogens has galvanized efforts to find alternative routes to combat bacterial virulence. One new approach entails interfering with the ability of bacteria to coordinate population‐wide gene expression, or quorum sensing (QS), thus inhibiting the production of virulence factors and biofilm formation. We have recently developed such a strategy by targeting LasR, the master regulator of QS in the opportunistic human pathogen Pseudomonas aeruginosa, through the rational design of covalent inhibitors closely based on the core structure of the native ligand. We now report several groups of new inhibitors, one of which, fluoro‐substituted ITC‐12, displayed complete covalent modification of LasR, as well as effective QS inhibition in vitro and promising in vivo results. In addition to their potential clinical relevance, this series of synthetic QS modulators can be used as a tool to further unravel the complicated QS regulation in P. aeruginosa . Abstract : Reaching a quorum : The inhibition of bacterial population‐wide synchronized gene expression, or quorum sensing (QS), has provided a new avenue to combat bacterial virulence. We present the rational design of improved covalent inhibitors targeting a key QS protein in the human pathogen P. aeruginosa, with in vitro and in vivo assays showing their promise as virulence inhibitors.